Peran Teknologi Informasi Dan Komunikasi Dalam Pendidikan Agama Hindu - Suprianto Suprianto; Rona Delpia (Institut Agama Hindu Negeri Tampung Penyang Palangkaraya, 2025)
Abstract The development of Information and Communication Technology (ICT) has significantly impacted the field of education, including Hindu religious education. This article explores the strategic role of ICT in facilitating Hindu religious learning through various forms, such as the digitalization of scriptures, interactive learning platforms, and social media as tools for education and religious outreach. ICT utilization enhances accessibility, interactivity, and students’ motivation in learning Hindu teachings. However, challenges remain, including limited infrastructure, gaps in teachers’ digital competence, and the lack of relevant and high-quality digital religious content. This article offers solutions such as digital literacy training for Hindu religious teachers, the development of Hindu-based digital learning platforms, and ongoing supervision of digital content. Therefore, ICT becomes an essential tool in addressing the challenges of Hindu religious education in the digital era. Keywords: Information and Communication Technology, Hindu Religious Education, Digital Learning, Social Media, Digital Scriptures.